W kwestii dziedziczenia wkładu gruntowego w rolniczej spółdzielni produkcyjnej - Geisler, Jerzy (Wydział Prawa i Administracji UAM, 1985)
The novelization of the Civil Code in the wake of the Act of 26 March, 1982, (Government Regulations and Laws Gazette nr 11 position 81), has introduced important changes regarding the succession to land contributions. The Act appoints all those to inherit land contributions who meet the preconditions expressed by art. 1087 § 1 point 1, 2, and 3 C.C., and. in cases of a lack, among the heirs, of persons meeting the condition expressed by art. 1087 § 1 point 1 C.C., the land contributions are further inherited by those expressed by art. 1087 § 2 C.C. Land contributions are inherited also by far-off descendants of the decedent, or the brothers and sisters of the decedent of their descendants, on the principle of the so-called specific replacement, on the basis of article 1060 and 1062 C.C. in connection to art. 1086 C.C, yet under the condition that they meet the precondition expressed by art. 1087 § 1 point 1 C.C. Article 1063 C.C. (in connection to art 1086 C.C.) can be fully made use of in successions to land contributions as it specifies the situations in which inheritance on general principles can take place, (i.e. on the basis of article 931 C.C. and the following). Article 1065 C.C. (in connection to art. 1086 C.C.) specifies those who might be appointed testamentary heirs to land contributions. In every case, anyone who meets the conditions entitling him or her to acquire an agricultural real estate by way of transfer of property (art. 1065 § 1 C.C), might be appointed and heir on the basis of the will. Further, someone who does not meet the above condition might still be appointed an heir, but he or she would have to be entitled to inherit the contribution by act, in the event of the decedent not leaving a will. The novelization of the Civil Code has encompassed other issues as well, among others, those connected to legacies of land contributions, the alienation of an inheritance of that of portions encompassing land contributions, of, finally, to the distribution of the inheritance.
On the Issue of Succession to Land Contributions in Co-operative Farms